Valoración de suelo forestado con caña guadua a través del servicio ecosistémico “capacidad hídrica”, comunidad Calada-Chone, como estrategia de conservación - Loor Solórzano, Ana María (2019)
This research aimed to assess forested land with Guadua cane through the ecosystem service “water capacity” in the Calada-Chone community, as a conservation strategy comprised four stages. In the first, an environmental, social and economic diagnosis of the study site was carried out, during the dry season, which included: the application of a questionnaire to the residents of the Calada community; comparisons between current and previous years maps of the study area; and identification of the water sources available in the forested soil with Guadua cane. In the second stage, the hydric capacity of forested and non-forested soil with Guadua cane was determined comparatively in the dry season, where soil samples were collected and analyzed, to know the levels of organic matter content, texture and water capacity in dry season. In the third stage, the environmental, social and economic value of the water capacity in the forested soil with Guadua cane was weighted. Finally, in the fourth stage a strategy was established for the conservation of the forested soil with Guadua cane. It was found that there are significant differences (p <0.05) between the forested land with guadua cane and the non-forested land, for the three parameters analyzed; which indicates that the forested land with Guadua cane has a greater environmental, social and economic value.